On the separation of coconuts: A modeling week study - Fitt, A; Please, C (2004)
The modus operandi of "modeling weeks" is explained and illustrated using a classical modeling week problem of subjecting coconuts to an external pressure before splitting them open, in the hope that the coconut meat will then separate easily from the shell. A range of modeling approaches is considered, and a poroelastic model is posed that allows the key problem parameters to be identified and calculated. We conclude that separation by this means is likely to be possible and relatively easy to accomplish.